Morphological structure and variations of fetal lateral meniscus: the significance in convenient diagnosis and treatment - Kabakci, Anil Didem Aydin; Buyukmumcu, MUSTAFA; BÜYÜKMUMCU, MUSTAFA; Akin, Duygu; Bilge, Onur (My University, 2019)
Purpose The aim of this study is to evaluate of morphometry of the lateral meniscus (LM) and determine incidence of the LM shapes. Methods This study was performed on fetal cadaver collection of Anatomy Department of Necmettin Erbakan University. Fifty human fetal cadavers (25 female, 25 male human fetal cadavers) were used in this study. Microdissection was performed. Morphometric measurements were performed. LM were classified into four types and five subtypes. Results In this study, it was identified that all parameters which were measured were found to be increased with gestational ages. Four morphological types and five morphological subtypes were determined. It was found that 12% of the LM were crescent-shaped, 66% of the LM were C-shaped, 14% of the LM were incomplete-disc-shaped, 2% of the LM were disc-shaped, 6% of the LM were variant C-shaped. Conclusions A few studies on fetal meniscal anatomy and its development were performed. Each new study is important for having detailed anatomy and development of the fetal menisci which will have both clinical and anatomical impacts during childhood and adulthood for orthopedic surgeons and anatomists, respectively. The most important results of this study were the detailed objective analysis of the macroscopic fetal growth of LM. It was significantly observed that four morphological types and five morphological subtypes of LM. The results of the present study related with both the observation of morphological development of the fetal meniscal anatomy, and its morphological variants, are important in terms of improving our knowledge, and clinical approach on the description, and the management of the symptomatic lateral discoid meniscus tears in children, adolescents, and adults. The clinical relevance of this study was that this classification of fetal menisci could ameliorate our current understanding of the morphology of lateral meniscus in adult, further.
Keywords: Knee